Analisis Pendekatan dan Platform Pengembangan Aplikasi Mobile: Sebuah Tinjauan Literatur Sistematis - Stefanie, Stefanie; Vincenzel, Davin; Agustin, Angelin; Farisi, Ahmad (Universitas Multi Data Palembang, 2025)
Currently, mobile applications is increasingly trending because they are easier to market so they are known to the public quicker. To create a mobile application that suits the needs, an appropriate development approach is needed. The research was conducted using the Systematic Literature Review (SLR) method on 23 mobile-based information system development papers. Systematic Literature Review method is carried out in several stages, namely planning, conducting, and reporting. The things studied are the approach used, development methods used, programming languages, databases, and the fields studied by each paper. Each paper must meet the Quality Assessment to answer the Research Question. With this, it will be known what approaches, development methods, programming languages and databases are most widely used by researchers in 2022-2024. From the review results, cross-platform was the most widely used approach during 2022-2024, so this can be used as a reference for other researchers to develop mobile applications.